USE OF DAMS METHOD IN TILLING WHEN PLANTING WHEAT - AL-Avebani, Marah Gh. (Diyala Agricultural Sciences Journal, 2015)
It was necessary to find a new and different way in tilling the soil equivalent to the difference that occurs in the amounts of rainfall within the same region or adjacent regions ، so came the way of dams in tilling the land ، which is working on the conversion of the land area or field to a semblance of small dams converged and cascading which ensures the benefit of water levels or rain ، whatever the quantities so was chosen piece of land a square-shaped area defined in the area adjacent to the University of Mosul and divided the land ostensibly without breaks real into three equal parts space almost as were planted the first part of the seeds of wheat in a manner of Agriculture in Brief the second way conversion of the land the field to semblance of small dams adjacent and successive As for the latter part was planting prose considered part comparison and after the completion of agriculture relying on rainwater only results were achieved this way significant increase evident in the average number of tillers per plant per average spike length (cm) to the extent awn and the average number of spikes in the plant and the total number of spikes per unit area and the average number of grains / spike and thousand kernel weight